God, humanity, and history : the Hebrew First Crusade narratives - Chazan, Robert (University of California Press, 2000)
Closely focused on the Hebrew First-Crusade narratives, this text examines the three surviving accounts of the crusaders assaults on the Rhineland Jewish communities in 1096. These accounts are compared with earlier Jewish history writing and with contemporary crusade historiography.
Keywords: Jews -- Germany -- History -- 1096-1147 -- Sources.; Jews -- Persecutions -- Germany -- History -- Sources.; Jewish martyrs -- Germany -- Biography -- Sources.; Crusades -- First, 1096-1099 -- Sources.; Germany -- Ethnic relations -- Sources.; Juifs -- Allemagne -- Histoire -- 1096-1147 -- Sources.; Juifs -- Persécutions -- Allemagne -- Histoire -- Sources.; Martyrs juifs -- Allemagne -- Biographies -- Sources.; Croisades -- 1re croisade, 1096-1099 -- Sources.; HISTORY.; RELIGION -- Judaism -- General.; Crusades; Ethnic relations; Jews; Jews -- Persecutions; Germany; Joden.; Kruistochten.; Kronieken (geschiedenis); Rheinland.; 1096-1147; Biography; Biographies; History; Sources; Biographies.